Are AI Wearables Vulnerable to Hacking? A Deep Dive into Digital Health Security Risks - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
Are AI Wearables Vulnerable to Hacking? A Deep Dive into Digital Health Security Risks The convergence of Artificial Intelligence (AI) and wearable tech...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning